Dispersion or concentration for the 1.5 generation? Destination choices of the children of immigrants in the US - Jamie Goodwin-White (Institute for the Study of Labor (IZA), 2006)
This paper examines determinants of inter-metropolitan destination choice for foreign-born and 1.5 generation adult children of immigrants in the US. An immigrant concentration-weighted accessibility parameter is included to assess the spatial structure of destination choice. A comparative origin-destination immigrant-native wage gap measure is also a strong determinant of destination choice, indicating the significance of relative labor market position. Although spatial assimilation perspectives would suggest that intergenerational social mobility should be connected with spatial dispersion, these models reveal the continuing importance of immigrant concentration for the 1.5 generation. When the destination concentration variable is added to reduced-form models, the positive effect of employment growth declines significantly, indicating that ethnic concentration may continue to be more important for the children of immigrants than more simply-framed economic conditions. Further, the increased model strength and parameter estimates associated with immigrant concentration and the accessibility measure suggest the spatial structure of destination choice depends on immigrant concentration at multiple scales - both to metro areas and to immigrant states or regions. The paper thus presents evidence for and suggests more attention to theorizing the geographic contexts of intergenerational immigrant incorporation, - 1.5 generation ; internal migration ; immigrant economic incorporation ; spatial assimilation
Keywords: J61; 330